Analysis of the Application of Deep Breathing Relaxation Techniques in Reducing Blood Pressure in Hypertension Patients - Eri Riana Pertiwi (Bantayang Omni Cendekia, 2024)
Background: Untreated hypertension will cause various cardiovascular problems. The hypertension treatment can be done using two methods, namely pharmacological and non-pharmacological. One way of non-pharmacological management is deep breathing relaxation therapy which focuses on breathing activity. Objective: This paper aims to see an analysis of the application of deep breathing relaxation to changes in blood pressure in hypertensive patients based on empirical studies in the last ten years Methods: The design of this research is a literature review of five journals that match the topic using the PICO framework method. The secondary data were taken from the Google Scholar database over the last ten years using an experimental design. Results: The results show that deep breathing relaxation techniques influence reducing blood pressure in hypertensive patients. Deep breathing relaxation is very effective and easy for hypertension sufferers to decrease blood pressure. Conclusion: Deep breathing relaxation is effective as a non-pharmacological therapy to reduce blood pressure in hypertensive patients.